High-performance flexible thermoelectric generator based on silicone rubber and cover with graphite sheet - Gobpant, Jakrit; Klongratog, Bhanupol; Rudradawong, Chalermpol; Sakdanuphab, Rachsak; Junlabhut, Prasopporn; Nuthongkum, Pilaipon; Limsuwan, Pichet; Sakulkalavek, Aparporn (My University, 2024)
Harvesting thermal energy through a flexible thermoelectric generator (FTEG) offers an excellent micro-power solution for energizing node sensors in the realm of Internet of Things (IoT) and wearable electronics. Nonetheless, current FTEG suffer from drawbacks including low efficiency, significant thermal resistance, and complex manufacturing procedures. In this study, a high-performance FTEG using silicone rubber was designed and fabricated using a straightforward process. The finite-element method was used to optimize the copper electrode thickness, and the bendable substrate layers with various thermal conductivity were studied for the first time. The copper electrode thickness of 0.1 mm was selected because it offers high flexibility and bendability while still providing a relatively high-power output. The 5 × 5 cm2 FTEG device was fabricated and covered with a bendable substrate. Silicon rubber (0.08 Wm−1K−1), silicon rubber added 5% graphene (0.14 Wm−1K−1), and graphite sheets (15 Wm−1K−1) were used as bendable substrates. The FTEG cover with graphite sheets has a maximum output voltage of 1.1 V under a temperature difference (ΔT) at 65 °C. Its maximum output power is 162.4 mW, corresponding to a power density of 6499.1 µW/cm2 under the same above ΔT. The experimental findings indicated that integrating a bendable substrate with high thermal conductivity and electrical insulation properties enhances the performance of the FTEG.
Keywords: Flexible thermoelectric generators; Graphite sheet; Silicone rubber